1981
DOI: 10.1007/bf01059343
|View full text |Cite
|
Sign up to set email alerts
|

A standard approach to compiling clinical pharmacokinetic data

Abstract: A standard format for a Clinical Pharmacokinetic Summary is proposed. It consists of a heading, tables, notes, and references for each drug reviewed. The table presents a unified and logical set of clinically useful population pharmacokinetic parameters. They concern four major areas: absorption, distribution, elimination, and the relationship of concentration to effect. Within each major group, parameters dealing with extents and rates of processes are given. Each such parameter is really two: a population me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 364 publications
0
5
0
Order By: Relevance
“…The importance of these methodological issues is illustrated by the numerous, statistically significant differences in mean parameter values between separate studies. The method proposed by Sheiner et al (1981) for pharmacokinetic summaries includes some correction for potential bias and is very suitable for integrating the data on amitriptyline. Table V contains all pertinent and major information from tables II to IV.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of these methodological issues is illustrated by the numerous, statistically significant differences in mean parameter values between separate studies. The method proposed by Sheiner et al (1981) for pharmacokinetic summaries includes some correction for potential bias and is very suitable for integrating the data on amitriptyline. Table V contains all pertinent and major information from tables II to IV.…”
Section: Discussion and Therapeutic Implicationsmentioning
confidence: 99%
“…The objective was to produce a single table that would provide a complete and critically assessed list of the pharmacokinetic and pharmacodynamic parameters of any drug. Because of insufficient data for amitriptyline, not all headings in the original paper of Sheiner et al (1981) could be included. Additional information is listed in table V, such as the distribution of amitriptyline or nortriptyline among the constituents of blood.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, DGX was reported in man to be excreted largely in urine as the unchanged form after iv administration of DGX, and its urinary recovery was 60 -80% [14,15]. Sheiner et al [16] reported that the total body, renal and metabolic clearances of DGX were 2.909 1.0, 1.64 90.50 and 0.79090.460 mL/min/kg (mean9…”
Section: Discussionmentioning
confidence: 97%
“…The study is being conducted according to number of individuals is required to participate, but the amount of the guidelines of the International Conference on Harmonization samples per individual is greatly reduced (to as few as two samples (ICH6), Good Clinical Practice guidelines (GCP), the declaration in some study designs). [50][51][52][53][54][55] This milder burden on the individual of Helsinki, the UNICEF convention on the rights of children, and patient makes population pharmacokinetics the ideal choice for the regulations of the ANMAT. studies in children.…”
Section: Pediatric Pharmacology Studiesmentioning
confidence: 99%